PREVALENCE OF SCHOLASTIC BACKWARDNESS AMONG LOWER PRIMARY SCHOOL STUDENTS IN ERNAKULAM DISTRICT, KERALA - SAJITHA SUSEELAN S,; SHEMI GEORGE, (The Journal of Research ANGRAU, 2025)
The study carried out in the year 2023 aimed to assess the extent of academic under achievement among lower primary school students. A cross-sectional study has been undertaken in both government and aided lower primary schools in the district, Ernakulam in Kerala.The students who exhibited poor scholastic performance were identified with the assistance of teachers and by reviewing annual school reports. IQ level of the identified scholastically backward students was measured using the Seguin Form Board Test, a standardized intelligence test. Results showed that out of 1084 lower primary students studied,166 (15.31%) students were scholastically backward, with 82 (16.84%) from the government schools and 84 (14.07%) from the aided schools. Most of the students had an IQ in the borderline range (70 – 79).The majority of scholastically backward students were boys and the highest number was in the age group 9-10, followed by the 8-9 and 7-8 years groups. Classes III and IV had the highest number of backward students.A significant majority 78 (46.99%) were from rural areas. There is a significant association between the area of residence and the type of school attended by scholastically backward students.